Allatotropin: An ancestral myotropic neuropeptide involved in feeding - Alzugaray, Maria Eugenia (2013)
Background: Cell-cell interactions are a basic principle for the organization of tissues and organs allowing them to perform integrated functions and to organize themselves spatially and temporally. Peptidic molecules secreted by neurons and epithelial cells play fundamental roles in cell-cell interactions, acting as local neuromodulators, neurohormones, as well as endocrine and paracrine messengers. Allatotropin (AT) is a neuropeptide originally described as a regulator of Juvenile Hormone synthesis, which plays multiple neural, endocrine and myoactive roles in insects and other organisms. Methods: A combination of immunohistochemistry using AT-antibodies and AT-Qdot nanocrystal conjugates was used to identify immunoreactive nerve cells containing the peptide and epithelial-muscular cells targeted by AT in Hydra plagiodesmica. Physiological assays using AT and AT- antibodies revealed that while AT stimulated the extrusion of the hypostome in a dose-response fashion in starved hydroids, the activity of hypostome in hydroids challenged with food was blocked by treatments with different doses of AT-antibodies. Conclusions: AT antibodies immunolabeled nerve cells in the stalk, pedal disc, tentacles and hypostome. AT-Qdot conjugates recognized epithelial-muscular cell in the same tissues, suggesting the existence of anatomical and functional relationships between these two cell populations. Physiological assays indicated that the AT-like peptide is facilitating food ingestion. Significance: Immunochemical, physiological and bioinformatics evidence advocates that AT is an ancestral neuropeptide involved in myoregulatory activities associated with meal ingestion and digestion.